Prenatal diagnosis of junctional epidermolysis bullosa associated with pyloric atresia. Issue 4 (April 1990) - Nazzaro, V; Nicolini, U; De Luca, L; Berti, E; Caputo, R
Abstract : Prenatal diagnosis of junctional epidermolysis bullosa associated with pyloric atresia was carried out in a couple at risk. Their two previous children had died during the first months of life of the same disorder despite surgery for the pyloric abnormality. Ultrastructural study of fetal skin biopsies obtained at 18 weeks' gestation showed dermal-epidermal separation at the lamina lucida level, while ultrasound showed marked stomach dilatation. Light microscopy of pyloric tissue obtained after termination showed the pyloric lumen to be replaced by loose connective tissue with no inflammatory reaction. Immunofluorescence studies on the skin specimens with the monoclonal antibody GB3, known to be absent in 'lethal' junctional epidermolysis bullosa skin, disclosed a marked positivity suggesting that the junctional epidermolysis bullosa in this case may be of the 'non-lethal' type.